Transcriptome- and genome-wide systematic identification of expansin gene family and their expression in tuberous root development and stress responses in sweetpotato (Ipomoea batatas) - Zhang, Jianling; Dong, Tingting; Zhu, Mingku; Du, Dan; Liu, Ranran; Yu, Qianqian; Sun, Yueying; Zhang, Zhihuan (Frontiers in Plant Science, 2024)
Expansins (EXPs) are essential components of the plant cell wall that function as relaxation factors to directly promote turgor-driven expansion of the cell wall, thereby controlling plant growth and development and diverse environmental stress responses. EXPs genes have been identified and characterized in numerous plant species, but not in sweetpotato. In the present study, a total of 59 EXP genes unevenly distributed across 14 of 15 chromosomes were identified in the sweetpotato genome, and segmental and tandem duplications were found to make dominant contribution to the diversity of functions of the IbEXP family. Phylogenetic analysis showed that IbEXP members could clustered into four subfamilies based on the EXPs from Arabidopsis and rice, and the regularity of protein motif, domain, and gene structures was in consistent with this subfamily classification. Collinearity analysis between IbEXP genes and related homologous sequences in nine plants provided further phylogenetic insights into the EXP gene family. Cis-element analysis further revealed the potential roles of IbEXP genes in sweetpotato development and stress responses. RNA-seq and qRT-PCR analysis of eight selected IbEXPs genes provided evidence of their specificity in different tissues, and showed that their transcripts were variously induced or suppressed under different hormone treatments (abscisic acid, salicylic acid, jasmonic acid, and 1-aminocyclopropane-1-carboxylic acid) and abiotic stresses (low and high temperature). These results provide a foundation for further comprehensive investigation of the functions of IbEXP genes, and indicate that several members of this family have potential applications as regulators to control plant development and enhance stress resistances of plants.